Ciência em debate? Uma análise das vozes no gênero notícia de popularização científica - Marcuzzo, Patrícia (2011)
There are several genres that disseminate scientific knowledge to society in the media sphere, such as television documentaries, printed news and reportages (MOTTA-ROTH, 2007, p. 3). This work focuses on the science popularization news genre, which presents scientific discoveries and quotes written published sources and interviews mainly with scientists. Therefore, science popularizartion texts are often framed as a debate between the source/voices, in which positive and negative evaluations of the popularized study are alternated (PARKINSON; ADENDORFF, 2005, p. 293). The objective of this work is to investigate to what extent the voices presented on science popularization news promote a debate on scientific discoveries. The corpus is formed by 60 science popularization news published in English, which were analyzed in the light of Critical Genre Analysis (MOTTA-ROTH, 2005; 2008c), including textual and contextual analysis. The results indicate that there is a multiplicity of voices that can be grouped into five enunciative standpoints: scientist/researcher, fellow researcher/technician/institution, government, public and the journalist himself/herself. However, the analysis indicates that two of these enunciative standpoints are more frequent and more prominent than the others: the scientist/researcher and the fellow researcher/technician/institution. The statements are inserted with the purpose of adding relevant content somehow related to the study reported in the news and rarely promote debate. The analysis points out that the journalists have a traditional perspective on science popularization (HILGARTNER, 1990, p. 519). Thus, it seems that we are still experiencing the second phase of science popularization, which began in the 20th century and is called Public Understanding of Science , in which the public is by no means truly participants, and the communicating process is mainly unidirectional, from science to society (JIANMIN, 2005).